SISTEM PEMBAYARAN ADMINISTRASI KEUANGAN MENGGUNAKAN TEKNOLOGI BARCODE BERBASIS CLIENT SERVER (STUDI KASUS DI SMK NEGERI 3 KENDAL) - Luluk Anas Mufarikah (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
SMK Negeri 3 Kendal uses a payment system that still uses a manual system, i.e inputting payment data using excel file and payment data through recording in the entry book daily so the Administrative Section of Urs. Finance is having difficulty recapitalizing income and making reports due to the calculation of invalid data and services that require a long time. Researchers use the Research and Development (R&D) method in developing payment systems SPI, Extracurricular and School Fees through the manufacture of final products using Visual Foxpro 9.0 and technology client-based barcode server. The results of testing by experts concluded that the payment system was declared valid.